Management of acutely injured cattle by on farm emergency slaughter: Survey of veterinarian views - McDermott, Paul; McKevitt, Aideen; Santos, Flávia H.; Hanlon, Alison (Frontiers in Veterinary Science, 2022)
Background: Fitness to transport is a key provision in animal welfare regulations in the European Union, and for the management of acutely injured cattle. Whilst treatment may be appropriate for some injuries, three common production outcomes for acutely injured cattle are; on farm emergency slaughter (OFES), casualty slaughter (CS) or euthanasia. The aims of this study were to evaluate the perceptions of veterinarians, working in Ireland, on the use of OFES for the management of acutely injured cattle and to evaluate the influence of capacity, willingness and opportunity on their ability to operate OFES. Methodology: Two online surveys of veterinarians working in Ireland, Private Veterinary Practitioners (PVPs) and Official Veterinarians (OVs), were conducted through QualtricsXM over a seven-week period between April and June of 2021. Quantitative and qualitative questions were developed and analysed using the tripartite framework of capacity, willingness, and opportunity to collect relevant data about the management of acutely injured cattle and the provision of OFES in Ireland by veterinarians. Results: 43 OVs and 85 PVPs participated in the survey. OVs regulated on average 4.2 abattoirs, of which 21.6% accepted OFES. Participants reported 343 and 377 OFES and CS, respectively, in 2020. 62.4% PVPs had not certified cattle for OFES, or CS. Limb fracture accounted for 79% OFES, 34.5% CS and 47.9% euthanized acutely injured cattle. 63.3% OVs and 44% PVPs were not aware of abattoirs providing OFES within 100km of their workplace. Lack of availability of OFES negatively associated with PVP knowledge of the procedure. Regulations and guidelines were the most common source of information on OFES. Conclusion: Increasing the availability of OFES may help to improve the management of acutely injured cattle, especially those with limb fractures that are unfit for transport.